A Novel Framework for Satellite Image Resolution Enhancement Using Wavelet-Domain Approach Based On Dt-Cwt and NLM (International Journal of Engineering and Computer Science, 2014)
In this paper, Resolution enhancement (RE) model has one of the biggest disadvantage (drawback) is losing high frequency contents (which results in blurring). Discrete wavelet transform based (DWT) RE scheme generates artifacts due to a DWT shift-variant property. For RE of the satellite images, here, new wavelet domain approach based on dual-tree complex wavelet transform (DT-CWT) and nonlocal means (NLM) is proposed. A satellite input image is decomposed by DT-CWT which is nearly shift invariant to obtain high-frequency sub bands. To interpolate the high-frequency sub bands and the low-resolution (LR) input images; in this paper the Lanczos interpolator is used. The high frequency sub bands are passed through an NLM filter to cater for the artifacts generated by DT-CWT. To  obtain a resolution-enhanced image we are combining the filtered high-frequency sub bands and the LR input image  by using inverse DT-CWT. Objective and subjective analyses show superiority of the new proposed technique over the conventional and state-of-the-art RE techniques.